Early human impact (5000–3000 BC) affects mountain forest dynamics in the Alps. (19th January 2015) - Schwörer, Christoph; Colombaroli, Daniele; Kaltenrieder, Petra; Rey, Fabian; Tinner, Willy; Austin, Amy
Summary The resilience, diversity and stability of mountain ecosystems are threatened by climatic as well as land‐use changes, but the combined effects of these drivers are only poorly understood. We combine two high‐resolution sediment records from Iffigsee (2065 m a.s.l.) and Lauenensee (1382 m a.s.l.) at different elevations in the Northern Swiss Alps to provide a detailed history of vegetational changes during the period of first pastoralism (ca. 7000–5000 cal. BP, 5000–3000 BC) in order to understand ongoing and future changes in mountain ecosystems. We use palaeoecological methods (fossil pollen, spore, microscopic charcoal and macrofossil analysis) as well as ecological ordination techniques and time‐series analysis to quantify the impact of fire and grazing on natural mountain vegetation at Iffigsee. Fire was used by Neolithic people to create pastures at timberline and clear forests for arable farming in the valley. This had a significant, long‐term effect on the mountain vegetation and a negative impact on keystone forest species such as Abies alba, Larix decidua and Pinus cembra. The mass expansion of Picea abies at ca. 5500 cal. BP (ca. 3500 BC) was facilitated by anthropogenic disturbance (fire, grazing and logging) causing an irreversible decline in Abies alba. Temperate Abies alba forests, which existed under warmer‐than‐today conditions, might be better adapted to projected climate change than today's drought‐sensitive Picea abies forests, especially under low anthropogenic disturbance following land abandonment. Synthesis. Human impact for millennia has shaped mountain vegetation in the Alps and still continues to have a large effect on today's species composition and distribution. Fire and traditional pastoralism have the potential to mitigate the effects of climate change, maintain species‐rich high‐alpine meadows and prevent biodiversity losses.